PENGARUH PENGUNGKAPAN KEY AUDIT MATTERS DAN CORPORATE GOVERNANCE TERHADAP AUDIT REPORT LAG - Dhani Faturrochman; Nur Cahyonowati (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of Key audit matters (KAM) disclosure and Corporate governance on Audit report lag (ARL). The independent variables consist of KAM, audit committee size, audit committee independence, audit committee expertise, audit committee meetings, board of commissioners size, and board of commissioners independence, while ARL serves as the dependent variable with company size, Big 4 auditors, and leverage as control variables. The population comprises non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024, with purposive sampling yielding 534 companies. Data were analyzed using panel data regression with a fixed effect model through EViews 13. The findings reveal that KAM disclosure, audit committee size, audit committee independence, audit committee expertise, board of commissioners size, and board of commissioners independence were found to have no significant effect on ARL, whereas audit committee meetings have a negative and significant effect on ARL.